Communication and information technologies annual - Robinson, Laura (Bingley, U.K. : Emerald, 2015)
Sponsored by the Communication, information technologies, and media section of the American Sociological Association, Volume 10 of the Communication and information technologies annual, Digital distinctions and inequalities, brings together nine studies of this increasingly important form of inequality. Drawn from four continents, the research provides a global overview of the current state of the field in different cultural contexts. As a whole, the volume illuminates the complexities of digital inequalities as they are manifested in groups and societies even when access is widespread. In their depth and breadth, the volume's contributions provide an indispensable guide to emergent forms of digital inequality as it rapidly evolves.
Cultural stratification on the internet : five clusters of values and beliefs among users in Britain / William H. Dutton, Grant Blank -- The third-level digital divide : who benefits most from being online? / Alexander J.A.M. van Deursen, Ellen J. Helsper -- What is new in the digital divide? Understanding internet use by teenagers from different social backgrounds / Marina Micheli -- From divides to capitals : an exploration of digital divides as expressions of social and cultural capital / Eduardo Villanueva-Mansilla, Teresa Nakano, Ine<U+0301>s Evaristo -- Mind the emotional gap : the impact of emotional costs on student learning outcomes / Kuo-Ting Huang, Laura Robinson, Shelia R. Cotten -- Online banking for the ages : generational differences in institutional and system trust / Saleem Alhabash ... [et al.] -- Inter-ethnic ties via mobile communications in homogeneous and ethnically mixed cities : a structural diversification approach / Yousaf Arie, Gustavo S. Mesch -- Contextualizing open Wi-Fi network use with multiple capitals / Christopher McConnell, Joseph Straubhaar -- Roads and roadblocks to digital inclusion : an analysis of a public policy program in California / Blanca Gordo.
Print version record
Keywords: Social Science -- Media Studies; Communication studies; Information technology -- Social aspects; Information technology -- Political aspects